KEHADIRAN JEPANG DI LAUT TIONGKOK SELATAN MELALUI KEBIJAKAN PROACTIVE CONTRIBUTION TO PEACE - Clarinda Inda Rahayu; Iwan Ridwan Zaelani (Indonesian Association for International Relations, 2022)
ABSTRACT Regional stability in the South China Sea plays an important role in ensuring the safety of regional trade. Although not involved in territorial disputes, Japan's presence in the South China Sea is related to energy and maritime interests. This research tries to investigate Japan's involvement in the South China Sea. Utilizing the qualitative research methods, this research reviews and analyzes Japanese policies, with observations through official Japanese government documents and other relevant literature. This research finds that Japan's main interest in the South China Sea is to maintain the stability of the Southeast Asian region in ensuring the security of maritime communication lines. Engaging a Balance of Power theory, this research sees at Japan's involvement in the South China Sea to achieve regional stability by increasing military capability and strengthen alliances with Us in the region. The results of this research reveal that Japan implements its security policy by adopting a more proactive approach as stated in the Proactive Contribution to Peace policy as an effort to balance China's assertiveness by strengthening diplomatic efforts in the defense aspect and increase security interaction with Southeast Asian countries. Keywords: Balance of Power, South China Sea, Japan, Proactive Contribution to Peace ABSTRAK Stabilitas kawasan di Laut Cina Selatan memegang peranan penting dalam menjamin keselamatan laju perdagangan regional. Meskipun tidak terlibat dalam sengketa wilayah, kehadiran Jepang di Laut Cina Selatan berkaitan dengan kepentingan energi dan jaur laut. Penelitian ini mencoba menelisik keterlibatan Jepang di Laut Cina Selatan. Dengan menggunakan metode deskriptif, penelitian ini meninjau dan menganalisis kebijakan Jepang, dengan melakukan observasi melalui dokumen resmi pemerintah Jepang dan dan literatur relevan lainnya. Penelitian ini menemukan bahwa kepentingan utama Jepang di Laut Cina Selatan adalah untuk menjaga stabilitas kawasan Asia Tenggara dalam menjamin keamanan jalur komunikasi laut. Menggunakan teori Balance of Power, penelitian ini melihat keterlibatan Jepang di Laut Cina Selatan untuk mencapai stabilitas kawasan dengan meningkatkan peran militer dan memperkuat aliansi dengan Amerika Serikat di kawasan tersebut. Hasil dari penelitian ini mengungkapkan bahwa Jepang melaksanakan kebijakan keamanan dengan mengadopsi pendekatan yang lebih proaktif yang tertuang dalam kebijakan Proactive Contribution to Peace sebagai upaya untuk menyeimbangkan ketegasan China dengan memperkuat upaya diplomatik di bidang pertahanan serta meningkatkan interaksi keamanan dengan negara-negara Asia Tenggara. Kata Kunci: Balance of Power, Laut China Selatan, Jepang, Proactive Contribution to Peace